Urbanscape Guidelines for Bahar-al-Toleye Mahallah in the Area of Razavi Holly Shrine (Global Journal of Human-Social Science, 2016)
Abstract not found
Keywords: wall needed; problem of readability; navigation; disorientation and ambiguity in orientation